The effects of conventional and unconventional monetary policies on the Euro area housing market - Zhang, Patric (2024)
This master’s thesis focuses on the effects of conventional and unconventional mone-tary policies on Euro area housing markets. The financial crisis of 2008 originated from over-heated U.S housing markets, where the initial problems in the housing markets had tremendous spill-over effects on the whole global economy. Housing accounts for over half of the Euro area household net worth (ECB, 2020b), and is usually acquired through bank debt financing, thus fluctuations in the Euro area housing prices can have contagious effects on the whole financial system.